What specific modes of internationalization influence SME innovation in Sub-Saharan least developed countries (LDCs)?. (January 2019) - Abubakar, Yazid Abdullahi; Hand, Chris; Smallbone, David; Saridakis, George
Abstract: Small and medium sized enterprises (SMEs) located in the least developed countries (LDCs), operate in distinctively hostile institutional environments compared to those in developed economies. Better understanding of the determinants of SME innovation in such environments is important for the development of private sector in LDCs, because innovative SMEs are crucial for sustainable economic growth. Yet, determinants of SME innovation in LDCs have hardly been studied. Considering the potential relevance of internationalization for SME innovation in LDCs, as means of overcoming domestic environmental constraints, this paper investigates the influence of foreign technology licensing, exports and imports on SME innovation in LDCs. The study employs data from 1058 manufacturing SMEs from Sub-Saharan LDCs - Djibouti, Tanzania, Uganda, Zambia and the Democratic Republic of Congo. The findings suggest that foreign technology licensing is found to be positively and statistically associated with SME product and process innovations in Sub-Saharan LDCs. Findings are compared with those from developed economies in order to identify distinctive features. The implication is that SMEs in Sub-Saharan LDCs need to be supported by different policies compared to developed economies. The results also show that R&D, firm size, sectoral characteristics and access to finance are important determinants of SME innovation. Highlights: Foreign technology licensing is positively and statistically associated with SME innovation in Sub-Saharan LDCs. R&D has strong impact on both produce and process innovation. Firm size and innovation are positively linked. Firms operating in low-tech sectors are less likely to innovate. Liquidity constraints stimulate SME innovation.